Legal Pluralism in Determining the Status of Illegal Children: A Study of the Constitutional Constitutional Court Decision Number 46/Puu-VII/2010 - Rosa Ezizya Febriani (Department of Sharia Economic Law, 2026)
This article examines the determination of the status of illegitimate children from the perspective of legal pluralism based on Constitutional Court Decision Number 46/PUU-VIII/2010. The decision reinterprets Article 43 paragraph (1) of Law Number 1 of 1974 concerning Marriage, by recognizing the civil relationship between illegitimate children with their biological father if it can be scientifically proven. This study uses a normative juridical method with a statutory and conceptual approach, complemented by a socio-legal approach. The results of the study indicate that the Constitutional Court decision represents a shift in the national legal paradigm from a formal approach to substantive protection of children's rights. However, in Islamic law, the lineage of illegitimate children remains only linked to the mother because the validity of the lineage is determined by a valid marriage contract. This difference demonstrates a form of combative legal pluralism between state law and Islamic law that interact within the framework of the Indonesian legal system.